Identifikasi Potensi Pembangkit Listrik Tenaga Hybrid (PLTH) Angin dan Surya di Kabupaten Aceh Besar - Fadhli Fadhli; Ichsan Syahputra (Jurnal Teknik Sipil Unaya, 2019)
The Wind and Solar Hybrid Power Plant (PLTH) research is expected to be able to contribute to assist the development of electricity supply in Aceh and gradually reduce and substitute the use of fossil energy. Hybrid Power Plant (PLTH) by combining wind energy and solar energy is a sustainable electricity supply technology that is increasingly popular because it is environmentally friendly and is not much constrained by land conversion. This research by measuring wind speed and solar radiation was carried out at selected locations in Aceh Besar District namely Lhoksedu, Lampuuk, Lambadeuk and Krueng Raya. The Lhokseudu location has a maximum wind speed of 6.3 m / sec and an average wind speed of 1 m / sec while solar radiation is a maximum of 764.90 W / m2, an average of 467.87 W / m2 and a minimum of 155.40 W / m2. Location Lampuuk maximum wind speed of 7.6 m / sec and average wind speed of 1.1 m / sec while maximum solar radiation is 1193 W / m2, average 678.74 W / m2 and minimum 30.20 W / m2. The Lambadeuk location has a maximum wind speed of 13 m / sec and an average wind speed of 1.3 m / sec while maximum solar radiation is 1589 W / m2, an average of 626.01 W / m2 and a minimum of 38.50 W / m2. The location of Krueng Raya is a maximum wind speed of 9.4 m / sec and an average wind speed of 3.1 m / sec while solar radiation is a maximum of 1019 W / m2, an average of 811.65 W / m2 and a minimum of 493.50 W / m2. Based on the results of data collection and analysis of wind speed and solar radiation that have been carried out including using secondary data / wind speed data from Blang Bintang BMKG Station at Sultan Iskandar Muda Airport and BMKG Indrapuri Station, it can be concluded that the more potential for PLTH development is the location Lambadeuk and Krueng Raya.